Effect of microencapsulated phase change material on the rheological and thermal properties of asphalt binder - Ozdemir, Ahmet Munir; Kok, Baha Vural; Yildirim, Furkan; Aydogmus, Ercan (Elsevier, 2025)
Asphalt binders are known for their pronounced sensitivity to temperature fluctuations, often leading to rutting under high temperatures and thermal cracking in colder conditions. While phase change materials (PCMs) have potential to regulate these thermal effects, their direct incorporation into binder poses challenges such as leakage and a lack of structural integrity. In this study, the effects of microencapsulated PCM additives on the rheological and thermal characteristics of asphalt binder was investigated. The results of Rotational Viscosity (RV), Temperature Sweep, Frequency Sweep and Bending Beam Rheometer (BBR) tests showed that PCM additions improve high-temperature performance by boosting viscosity and stiffness, and also help reduce brittleness at low temperatures. Supporting chemical analyses such as FTIR, TGA-DSC, and SEM confirmed both the successful integration and thermal stability of the microencapsulated PCM within the binder matrix. Further evaluation using master curves and the Cross Model highlighted a notable increase in zero-shear viscosity, particularly with an 8 % PCM content, along with improved flow consistency across varying temperatures. Additionally, thermal behavior assessments using a custom-designed experimental setup showed that PCM incorporation had a significant effect on the binder's temperature-time response. The duration to achieve peak temperature was extended, while both the heating rate and cooling slope were reduced, leading to a decrease in the overall thermal load in samples containing PCM. The area under the curve and thermal lag times indicated that PCM effectively absorbs heat during phase transitions, thereby dampening temperature fluctuations and ensuring a more stable thermal response of the binder.
Keywords: Asphalt; Encapsulated phase change material; Rheology; Thermal regulation; Dynamic shear rheometer